Respuesta :

Answer : 3v ² +4v+5
Combine the like terms : 5+4v+3v ²
Rewrite the expression: 3v ² +4v+5

Answer:

[tex]\boxed{3} \;v^2 + \boxed{4}\;v + \boxed{5}[/tex]

Step-by-step explanation:

Original expression: 3 + v + 4v² + 2 - v² +3v

Combining like terms in a equation means grouping them together to get a single instance of that term instead of multiple

For example in this expression we can see there is a +4v² and a -v². Group these together and simplify algebraically to get a single v² expression. Do the same with the others.

3 + v + 4v² + 2 - v² +3v

Group the v² terms together to get 4v² - v² = 4v² - 1v² = 3v²  (v² == 1v²)
(since the variables are same we can simply add the coefficients

Now group the v terms and simplify

3 + v + 4v² + 2 - v² + 3v
v + 3v = 4v

Finally group the constants
3 + v + 4v² + 2 - v² +3v
3 + 2 = 5

So the final expression is

3 + 4v + 5

The numbers are what you put in the boxes for each

Usually this process is done in a few steps
3 + v + 4v² + 2 - v² +3v

= (4v² - v²) + (v + 3v) + (3 +2)
= 3v² + 4v + 5

ACCESS MORE